UJI KELIMPAHAN BAKTERI COLIFORM PADA MAKANAN JAJANAN BAKSO TUSUK YANG DIJUAL DI LINGKUNGAN SDN 82 KUDAMATI DAN SDN 2 TANAH TINGGI AMBON - Aknes Tahya; M Kaihena; Theopilus Watuguly (BIOPENDIX, 2018)
Background: Snack food is part of food that is inseparable from the community. Snack food consists of various types, one of which is skewer meatballs. Skewers are a type of snack food made from flour and meat that is round and then boiled until cooked, has a savory and chewy taste. One of the bacteria that often contaminates snacks is coliform bacteria. Coliform bacteria is a group of rod-shaped gram negative bacteria. Method: The sample used in the study was skewered meatball samples taken at the location of SDN 82 Kudamati and SDN 2 Tanah Tinggi Ambon. Testing for the presence of coliform bacteria was carried out at the Indonesian Institute of Research and Standardization Laboratory in Ambon. The type of research used is descriptive. Calculation of the number of bacterial colonies using the standard Total Plate Count (TPC). Results: The study showed that the two positive samples contained coliform bacteria with the highest number of coliform bacteria colonies in code A1 1.55 x 105 at location A SDN 82 Kudamati and the lowest at code B1 1.49 x 103 at location B SDN 2 Tanah Tinggi. If compared with SNI for processed meat and chicken products is 1 x 105 colonies / gram, which means the highest number of colonies cannot be consumed. Conclusion: Skewers meatball snacks sold in SDN 82 Kudamati and Ambon Tanah 2 Elementary School 2, positive for coliform bacteria